An unusual case of extensive chondrosarcoma of nasal septum - Jain, Satish; B., Harikrishan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Chondrosarcoma is a very rare malignant tumour of nasal cavity. It is seen commonly in middle aged men. The definitive treatment is surgical resection with wide margins. Radiation and chemotherapy are reserved for residual or recurrent disease and as palliative treatment. Here we present a case of Grade II mesenchymal chondrosarcoma involving both nasal cavities extending into ethmoid, frontal and sphenoid sinuses with intracranial extension and also its surgical management.